Turbidities in the Upper Bhuban Member of the Sitakund anticline, Chittagong, Southestern Bangladesh (Journal of Life and Earth Science, 2011)
The Upper Bhuban Member in the Sitakund anticline, Chittagong, Southeastern Bangladesh is constituted by the light gray, light yellow and greenish gray sandstone and siltstone with dark gray, bluish black and black finely laminated silty shale to shale. The lithofacies of massive sandstone(Sm), turbidite sandstone (ST), flat bedded sandstone-siltstone (Sh), ripple cross laminated sandstone-siltstone (Sr), laminated sandstone-siltstone (Sl), lenticular laminated sandstone-siltstone-shale (Sll), wavy laminated silty shale to shale (Fw), laminated shale (Fl) with sub-facies black shale (Flbk) and blue shale (Flb) and mudstone (Fm) have been delineated in this member. Based on genetic aspects the facies are grouped into (1) turbidity generated - and (2) deep marine basin plain facies association. The medium to fine grained facies Sm and ST with or without Sh, Sr, Sl Sll Fw and Fm facies constitutes the turbidity generated facie association. The deep marine basin plain facies association is characterized by the monotonous hemi-pelagic bluish black shale (subfacies Flb) and pelagic black shale (subfacies Flbk) with rare to scare silty stringers of facies Sh, Sr, Sl, Sll and Fw. The facies Sm is turbidity channel in the inner part of medial fan and the complete ST sequence indicates channelized forms, while incomplete ones have been identified as channel or interchannel deposits in medial to distal fan. The facies Flb and Flbk denote deep marine environments above and below the carbonate compensation depth, where the lithofacies facies Sh, Sr, Sl, Sll and Fw were deposited as distal turbidites. The facies sequence of medial to distal fan and deep marine basin plain were repeated and randomly juxtaposed one upon other due to instability of basin probably by faulting along Dauki and adjoining area accompanied by sea level change. The paleoflow pattern indicates that the dominant source of detrius was the Shillong plateau along with minor contribution from the Himalayas and Arakan Yoma Folded Belt. Keywords: Turbidites; Upper Bhuban Member; Sitakund anticline; SE Bangladesh. DOI: 10.3329/jles.v2i2.7491 J. Life Earth Sci., Vol. 2(2) 1-16, 2007